К истории бронепоездов (проблемы классификации и терминологии) - Ромадин, С.В. (Питання історії науки і техніки, 2009)
При розробці питань історії бронепоїздної техніки дослідники стикаються з відсутністю чітко устояної термінології, оскільки вона постійно корегувалась й еволюціонувала під впливом безлічі факторів. Розгляду відповідних питань присвячена дана стаття. By development of questions of history of the armored train equipment researchers collide
with absence of precisely settled terminology as it constantly was corrected and changed
under influence of set of factors. Given clause is devoted to consideration of these questions.